Overexpression of endothelial nitric oxide synthase suppresses features of allergic asthma in mice - Broeke, Robert Ten (BioMed Central, 2006)
BACKGROUND: Asthma is associated with airway hyperresponsiveness and enhanced T-cell number/activity on one hand and increased levels of exhaled nitric oxide (NO) with expression of inducible NO synthase (iNOS) on the other hand. These findings are in paradox, as NO also relaxes airway smooth muscle and has immunosuppressive properties. The exact role of the endothelial NOS (eNOS) isoform in asthma is still unknown. We hypothezised that a delicate regulation in the production of NO and its bioactive forms by eNOS might be the key to the pathogenesis of asthma. METHODS: The contribution of eNOS on the development of asthmatic features was examined. We used transgenic mice that overexpress eNOS and measured characteristic features of allergic asthma after sensitisation and challenge of these mice with the allergen ovalbumin. RESULTS: eNOS overexpression resulted in both increased eNOS activity and NO production in the lungs. Isolated thoracic lymph nodes cells from eNOS overexpressing mice that have been sensitized and challenged with ovalbumin produced significantly less of the cytokines IFN-γ, IL-5 and IL-10. No difference in serum IgE levels could be found. Further, there was a 50% reduction in the number of lymphocytes and eosinophils in the lung lavage fluid of these animals. Finally, airway hyperresponsiveness to methacholine was abolished in eNOS overexpressing mice. CONCLUSION: These findings demonstrate that eNOS overexpression attenuates both airway inflammation and airway hyperresponsiveness in a model of allergic asthma. We suggest that a delicate balance in the production of bioactive forms of NO derived from eNOS might be essential in the pathophysiology of asthma.